G20: Concert of great powers or guardian of global well-being? - Thomas Fues; Dirk Messner (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
Eight years after its formation at the leaders' level, the Group of 20 (G20) has consolidated its status as the power centre of global economic governance. The informal club of 19 nation-states plus the European Union has set itself ambitious goals. They want to lead the global economy towards “strong, sustainable and balanced growth”. Opinions on the success and the broader implications of the G20 diverge widely in global conversations (Bradford & Lim, 2011). Critical voices point to the fundamental lack of legitimacy for the self-selected group of global powers. Other sceptics call into question the effectiveness of the G20 in balancing national interests and managing the world economy. In a more positive assessment, the G20 is given credit for moderating trade conflicts and averting currency wars. Sympathisers also acknowledge the G20's role in nudging the global system towards a post-Western constellation by integrating large (re-)emerging economies beyond the Organisation for Economic Co-operation and Development (OECD). Clearly, the G20 is not mandated, nor does it operate under the guidance of the United Nations (UN), the universal body of ultimate legitimacy. Looking at the G20 from the perspective of effective global governance, the big question to ask is: Do member states see their group as a concert of great powers or are they ready to act as guardians of global well-being? The latter would imply that the G20 anchors its entire work in three transformational documents adopted by world leaders last year at the UN: the 2030 Agenda for Sustainable Development, the Addis Ababa Action Agenda and the Paris Climate Agreement. The G20 at the leaders' level has come about in response to the severe financial disorder of 2008. It adopted the membership formula of the G20 of finance ministers, which was set up by governments from all parts of the world in 1999 with a similar intent of crisis management (regarding the Asian financial crisis of that time). The 19 member countries plus the European Union represent a diverse cosmos of old and new economic powerhouses, selected more on the economic exigencies of the outgoing 20th century than on the basis of criteria that would reflect representativeness and the preparedness to live up to international responsibilities. While Europe is strongly represented, other regions lack adequate inclusion. From Sub-Sahara Africa, only South Africa was selected, and Saudi Arabia is the sole member from the Arab world (Fues & Wolff, 2010). The strengths, as well as weaknesses, of the G20 lie in its informality and flexibility. The group has no legal status, no charter and no permanent secretariat. It is driven by annual summits, which are hosted by yearly rotating presidencies. Two parallel tracks – under the guidance of sherpas and finance ministers, respectively – structure the process (see Box 1). Over time, the G20 has established a myriad of working groups and work streams, such as on infrastructure, development, employment and trade. As a result, the overall coherence of the G20 architecture leaves much to be desired (Dubey, 2015). The workload of attending to an ever-increasing number of policy fields stretches the capacities of most national bureaucracies to the limit.
Keywords: 330; Agenda 2030; Regional + global + transnational governance